2018
DOI: 10.3390/toxins10060235
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Microcystin-LR-Induced Testis Germ Cell Apoptosis in Rats via SIRT1 Signaling Pathway Activation

Abstract: Microcystin-leucine arginine (MC-LR), a cyclic heptapeptide produced by cyanobacteria, is a strong reproductive toxin. Studies performed in rat Sertoli cells and Chinese hamster ovary cells have demonstrated typical apoptosis after MC-LR exposure. However, little is known on how to protect against the reproductive toxicity induced by MC-LR. The present study aimed to explore the possible molecular mechanism underlying the anti-apoptosis and protective effects of resveratrol (RES) on the co-culture of Sertoli–g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…The identification of co‐cultured Sertoli‐germ cells was performed in our previous studies and is not shown here . The inhibition rate of MC‐LR on co‐cultured Sertoli‐germ cells for 24 hours was detected by CCK‐8.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The identification of co‐cultured Sertoli‐germ cells was performed in our previous studies and is not shown here . The inhibition rate of MC‐LR on co‐cultured Sertoli‐germ cells for 24 hours was detected by CCK‐8.…”
Section: Resultsmentioning
confidence: 98%
“…The inhibition rate of cell proliferation was detected by CCK‐8 kit as described previously . In detail, 100 μL cell suspension was added to 96‐well plate with a minimum inoculum density of 1000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations